2000
DOI: 10.1111/j.1471-0528.2000.tb10406.x
|View full text |Cite
|
Sign up to set email alerts
|

Postmenopausal hormone replacement improves proteinuria and impaired creatinine clearance in type 2 diabetes mellitus and hypertension

Abstract: Objective To determine whether hormone replacement therapy can reverse established renal microvascular damage in type 2 diabetes and hypertension.Design Prospective, single centre clinical trial.Setting Outpatient clinics. ParticipantsMethods Administration of a cyclic combination of oestradiol and norgestrel orally for 3.5 monthly cycles. ResultsComparing the baseline values, mean (SD) 24-hour urine protein excretion was reduced from 0.452 g (0-039) to 0.370 g (0-047) (P c 0.01) and creatinine clearance was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 24 publications
7
43
0
3
Order By: Relevance
“…These observations imply an association between onset of sexual maturity and the development and progression of diabetic nephropathy. Short-term administration of estrogen alone 55,56 or together with norgestrel (a synthetic progestin) was found to reduce proteinuria and improve creatinine clearance in diabetic and hypertensive postmenopausal women. 57 Short-term treatment with raloxifene limits the progression of albuminuria in postmenopausal women with type 2 DM.…”
Section: Estrogens and Diabetic Nephropathymentioning
confidence: 99%
“…These observations imply an association between onset of sexual maturity and the development and progression of diabetic nephropathy. Short-term administration of estrogen alone 55,56 or together with norgestrel (a synthetic progestin) was found to reduce proteinuria and improve creatinine clearance in diabetic and hypertensive postmenopausal women. 57 Short-term treatment with raloxifene limits the progression of albuminuria in postmenopausal women with type 2 DM.…”
Section: Estrogens and Diabetic Nephropathymentioning
confidence: 99%
“…14,15 According to this data, short-term administration of estrogen was found to improve proteinuria and creatinine clearance in diabetic and hypertensive postmenopausal women. 16 Another study supports the beneficial effect of estrogens on insulin action, which was demonstrated to be greater in premenopausal women. 17,18 In this study, an animal model of ovariectomy with sepsis and diabetes was used to investigate the effects on immunologic response, mortality, and tissue oxidant status.…”
Section: Introductionmentioning
confidence: 76%
“…Vasküler sistemle iliflkili olan renal mikrovasküler sistem üzerine s›n›rl› bilgi olup, özellikle cerrahi menopoz sonras› östrojen eksikli¤inin veya farmakolojik dozlarda östrojen replasman tedavisinin (ERT) bu sistem üzerine etkisi tam olarak bilinmemektedir (25) .…”
Section: G‹r‹fiunclassified
“…Hiperkolesterolemik ‹mai ratlarda yap›lan çal›flmaya ters olarak obez Zucker ratlarda ise anormal proteinürinin, ooferektomi sonras› normale döndü¤ü gösterilmifltir (24) . (25) .…”
Section: Ratlarda Yap›lan çAl›flmalarda Ert'nin Hiperlipidemik Analbuunclassified